2015
DOI: 10.1016/j.ifacol.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Profit and Risk Measures in Oil Production Optimization∗∗This research project is financially supported by the Danish Research Council for Technology and Production Sciences. FTP Grant no. 274-06-0284 and the Center for Integrated Operations in the Petroleum Industry at NTNU.

Abstract: In oil production optimization, we usually aim to maximize a deterministic scalar performance index such as the profit over the expected reservoir lifespan. However, when uncertainty in the parameters is considered, the profit results in a random variable that can assume a range of values depending on the value of the uncertain parameters. In this case, a problem reformulation is needed to properly define the optimization problem. In this paper we describe the concept of risk and we explore how to handle the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Control risks relate to the setting of production rates from individual wells as well as daily production targets. Capolei, Foss and Jørgensen (2015, p.215) identified that, for new wells, these risks are related to the high uncertainty in seismic data, core samples, and borehole logs (Capolei, Foss et Jørgensen, 2015). Svensson (2000) identified that demand risks are related to downstream supply chain activities, including market risk due to price instability and market fluctuations (Svensson, 2000).…”
Section: Supply Chain Planning Under Uncertaintymentioning
confidence: 99%
“…Control risks relate to the setting of production rates from individual wells as well as daily production targets. Capolei, Foss and Jørgensen (2015, p.215) identified that, for new wells, these risks are related to the high uncertainty in seismic data, core samples, and borehole logs (Capolei, Foss et Jørgensen, 2015). Svensson (2000) identified that demand risks are related to downstream supply chain activities, including market risk due to price instability and market fluctuations (Svensson, 2000).…”
Section: Supply Chain Planning Under Uncertaintymentioning
confidence: 99%
“…Hanssen et al [57] formulated a stochastic reservoir optimization problem based on CVaR to handle oil production constraints. It was further extended to consider multiple risk scenarios [58]. For large ensemble realizations, retrospective optimization was found to be an optional technique [59].…”
Section: Gradient Based Waterflood Optimizationmentioning
confidence: 99%
“…MO includes uncertainty in the optimization framework, but the optimized solution does not lead to a reduced uncertainty in the achieved NPV. For better uncertainty handling of these MOOs, we are inspired by the seminal work of "risk-return" portfolio management (Markowitz 1952), which has been applied to robust waterflooding optimization under geological uncertainty by Capolei et al (2015b), to consider a riskaverse MVO objective. In MVO, the risk is quantified by the variance of the NPV distribution.…”
Section: Introductionmentioning
confidence: 99%
“…By changing the NPV objective, these optimization methods provide an indirect or ad hoc way of balancing the short-term and the long-term economic objectives. In Capolei et al (2015b), a bicriterion MVO function has been optimized and key economic indicators have been given. We consider a single-objective MVO to investigate whether, by explicit handling of uncertainty in model-based economic optimization, the balance between shortterm and long-term gains can be naturally obtained.…”
Section: Introductionmentioning
confidence: 99%